Plant life of the Dolomites : atlas of flora - Pignatti, Erika; Pignatti, Sandro (Veröffentlichungen des Naturmuseums Südtirol, Bozen ;, 2016)
This volume offers distribution maps of over 2200 individual species living in the Dolomite area, presenting detailed records on the local range of every species growing in the area studied, from the Puster Valley to the Piave River. The data was collected on the basis of a multiple field observations carried out over several decades. After dividing the area into approx. 200 quadrants, a nearly complete census of the species present was obtained for each quadrant. The evaluation and synopsis of this extensive set of data, which is presented in the form of a chorological atlas in keeping with international standard methods, allows the area to be accurately compared with other parts of the Alps. In addition to the chorological atlas and floristic inventory, a list of synonyms and toponyms of the three languages used in the analyzed territory, an expanded list of updated scientific names, and some helpful remarks on various Dolomites species are included. Lastly, the book explores how species can be considered as landscape bioindicators. This third volume of the work Plant Life of the Dolomites complements the main volume Vegetation Structure and Ecology and the volume Vegetation Tables, which presents essential data at the plant association level.